Group IVA Cytosolic Phospholipase A(2) Regulates the G(2)-to-M Transition by Modulating the Activity of Tumor Suppressor SIRT2 - Movahedi Naini, Said (Mol Cell Biol, 2015)
The G(2)-to-M transition (or prophase) checkpoint of the cell cycle is a critical regulator of mitotic entry. SIRT2, a tumor suppressor gene, contributes to the control of this checkpoint by blocking mitotic entry under cellular stress. However, the mechanism underlying both SIRT2 activation and regulation of the G(2)-to-M transition remains largely unknown. Here, we report the formation of a multiprotein complex at the G(2)-to-M transition in vitro and in vivo. Group IVA cytosolic phospholipase A(2) (cPLA(2)α) acts as a bridge in this complex to promote binding of SIRT2 to cyclin A-Cdk2. Cyclin A-Cdk2 then phosphorylates SIRT2 at Ser331. This phosphorylation reduces SIRT2 catalytic activity and its binding affinity to centrosomes and mitotic spindles, promoting G(2)-to-M transition. We show that the inhibitory effect of cPLA(2)α on SIRT2 activity impacts various cellular processes, including cellular levels of histone H4 acetylated at K16 (Ac-H4K16) and Ac-α-tubulin. This regulatory effect of cPLA(2)α on SIRT2 defines a novel function of cPLA(2)α independent of its phospholipase activity and may have implications for the impact of SIRT2-related effects on tumorigenesis and age-related diseases.